Hormone replacement treatment regimen is associated with a higher risk of hypertensive disorders of pregnancy in women undergoing frozen-thawed embryo transfer - Fan, Lijuan; Li, Na; Liu, Xitong; Li, Xiaofang; Cai, He; Pan, Dan; Wang, Ting; Shi, Wenhao; Qu, Pengfei; Shi, Juanzi (Frontiers in Endocrinology, 2023)
Introduction: In frozen-thawed embryo transfer (FET) cycles, hormone replacement treatment (HRT) was associated with a higher risk of hypertensive disorders of pregnancy (HDP) compared with natural cycles (NC). Multiple pregnancy was a risk factor for HDP and several studies did not conduct subgroup analysis of singleton pregnancy and multiple pregnancy. Objective: To investigate whether HRT regimen could be a risk factor for HDP in women undergoing FET cycles in singleton and twin pregnancies. Methods: A retrospective cohort study at a tertiary hospital, including a total of 9120 women who underwent FET and achieved ongoing pregnancy; 7590 patients underwent HRT-FET and 1530 NC-FET. The main outcome was HDP. HDP were analyzed for singleton and twin pregnancies, respectively. Results: In the singleton pregnancy, the risk of HDP in the HRT-FET group was significantly higher than that in the NC-FET group (6.21% vs. 4.09%; P=0.003). After adjusting for female age oocyte pick up, female age at FET and body mass index (BMI), HRT was found as a risk factor for HDP (adjusted odds ration [aOR]: 1.43; 95% confidence interval [CI]: 1.07 to 1.91; P=0.017). In the multiple pregnancy, the risk of HDP in the HRT-FET and NC-FET groups was similar. Conclusion: HRT was associated with a higher risk of HDP in women who underwent FET and achieved singleton pregnancy.